Species composition of the international shark fin trade assessed through a retail‐market survey in Hong Kong. Issue 2 (15th December 2017) - Fields, Andrew T.; Fischer, Gunter A.; Shea, Stanley K. H.; Zhang, Huarong; Abercrombie, Debra L.; Feldheim, Kevin A.; Babcock, Elizabeth A.; Chapman, Demian D.
Abstract: The shark fin trade is a major driver of shark exploitation in fisheries all over the world, most of which are not managed on a species‐specific basis. Species‐specific trade information highlights taxa of particular concern and can be used to assess the efficacy of management measures and anticipate emerging threats. The species composition of the Hong Kong Special Administrative Region of China, one of the world's largest fin trading hubs, was partially assessed in 1999–2001. We randomly selected and genetically identified fin trimmings ( n = 4800), produced during fin processing, from the retail market of Hong Kong in 2014–2015 to assess contemporary species composition of the fin trade. We used nonparametric species estimators to determine that at least 76 species of sharks, batoids, and chimaeras supplied the fin trade and a Bayesian model to determine their relative proportion in the market. The diversity of traded species suggests species substitution could mask depletion of vulnerable species; one‐third of identified species are threatened with extinction. The Bayesian model suggested that 8 species each comprised >1% of the fin trimmings (34.1–64.2% for blue [ Prionace glauca ], 0.2–1.2% for bull [ Carcharhinus leucas ] and shortfin mako [ Isurus oxyrinchus ]); thus, trade was skewed to a few globally distributed species. Several other coastal sharks, batoids, and chimaeras are in the trade but poorly managed. Fewer than 10 of the species we modeled have sustainably managed fisheries anywhere in their range, and the most common species in trade, the blue shark, was not among them. Our study and approach serve as a baseline to track changes in composition of species in the fin trade over time to better understand patterns of exploitation and assess the effects of emerging management actions for these animals. Abstract : Article impact statement : One‐third of species traded in the Hong Kong shark fin market are threatened with extinction and <10 modeled have sustainably managed fisheries.